Uprise of Periodical Samizdat: Phenomenon of Soviet Dissidentism and Lithuaninian Catholic Movement - Jaseliūnas , Egidijus (Genocidas ir rezistencija, 2002)
Comparative analysis of the periodical Samizdat as a dissident movement is based on a strict definition of the dissident movement. This definition reflects the dissident movement notions presented in the works of P. Reddaway, V. Shlapentokh, D. Spechler, R. Tökes and G. Ionescu and is defined as follows: the essential attribute of the Soviet dissident movement was to pursue government control independent activities. Their purpose was not to change the existing regime, but to cause changes within the system. The dissidents did not restrict only to the activities permissible by the political system, but would often exceed the limits tolerated by the government.
Keywords: Soviet occupation; resistance; civil resistance; samizdat; dissidents